К фауне кровососущих комаров Керченского полуострова - Алексеев, Е.В. (Вестник зоологии, 1973)
The article deals with the data on fauna ecology and distribution of blood-sucking midges in the Kerch peninsula. The species found for the first time in the Crimean region are given.